Will the Internet fragment? : sovereignty, globalization, and cyberspace - Mueller, Milton (Cambridge, UK ; Malden, MA : Polity Press, 2017)
Coming undone? -- A taxonomy of "fragmentation" -- The illusion of technical fragmentation -- Alignment: cyberspace meets sovereignty -- Confronting alignment -- Popular sovereignty in cyberspace.